Analisis Pengaruh Penambahan Inclined Serration Flat-Plate Pada Trailing Edge Propeller Terhadap Tingkat Kebisingan dan Nilai Thrust - Firliandini Pralinda Sundari; Elisabeth Anna Prattiwi; Bangga Dirgantara Adiputra; Eli Kumolosari; Okto Dinaryanto (Angkasa: Jurnal Ilmiah Bidang Teknologi, 2026)
The increasing use of drones in Indonesia potentially causes noise pollution due to propeller-generated sound. One widely studied approach to reducing propeller noise is trailing edge modification. Noda et al. (2019) showed that serrated gurney flaps can reduce noise at low RPM with minimal impact on thrust, although their effectiveness decreases at higher RPM. One factor that has not been considered is the serration’s installation angle. This study investigates the effect of adding an inclined serration flat-plate on the noise and thrust of a propeller. Numerical simulations were conducted using the frozen rotor method with the k-ω SST turbulence model and the Ffwocs-William and Hawking acoustic analogy. The results show that the serration increased thrust up to 41.707% at 10,000 RPM. In contrast, the trend of Sound Pressure Level (SPL) towards frequency generally increased, leading to a rise in Overall SPL (OASPL) up to 3.497 dB at 10,000 RPM